2023
DOI: 10.3390/brainsci13040540
|View full text |Cite
|
Sign up to set email alerts
|

Positive Touch Deprivation during the COVID-19 Pandemic: Effects on Anxiety, Stress, and Depression among Italian General Population

Abstract: Physical distancing due to the COVID-19 Pandemic has limited the opportunities for family members, friends, and significant others to show physical affection (i.e., hugs, kisses, caresses, holding hands) during social interactions. The present study investigated the effects of positive touch and psychological distress in 991 Italian participants (Mage = 34.43, SD = 14.27). Results showed the frequency of hugs with the cohabiting partner significantly decreased the symptoms of depression (β = −1.187, p = 0.018,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Literature shows that female sex and advanced-stages cancers are among the major risk factors for high psychological distress [ 12 ]. The widespread of COVID-19 pandemic has had an unprecedented impact on both the general population [ 13 16 ] and cancer patients [ 17 , 18 ]. In addition, the interruption of medical screening due to the COVID-19 pandemic caused a significant increase in the diagnosis of advanced-stages cancers and a consequent reduction in the prevalence of early forms in Italian women [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows that female sex and advanced-stages cancers are among the major risk factors for high psychological distress [ 12 ]. The widespread of COVID-19 pandemic has had an unprecedented impact on both the general population [ 13 16 ] and cancer patients [ 17 , 18 ]. In addition, the interruption of medical screening due to the COVID-19 pandemic caused a significant increase in the diagnosis of advanced-stages cancers and a consequent reduction in the prevalence of early forms in Italian women [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human contact through physical touch is a core element in social bonding, which facilitates psychosocial well-being [ 1 , 2 , 3 ]. Indeed, researchers have found that positive touch, which has decreased in the context of a global pandemic, may affect psychological well-being [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human contact through physical touch is a core element in social bonding, which facilitates psychosocial well-being [ 1 , 2 , 3 ]. Indeed, researchers have found that positive touch, which has decreased in the context of a global pandemic, may affect psychological well-being [ 3 ]. Physical touch enables the communication of motivations and emotions, and early maternal touch is associated with the age-appropriate development of infant social brain areas and secure attachment [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%